KENYAMANAN TERMAL DALAM PENGENDALIAN PENYERAPAN PANAS BANGUNAN (STUDI KASUS: GEDUNG OLAHRAGA KISARAN) - Dinnie Ananda Rizky (Yayasan Nusantara Hasana Berdikari, 2026)
GOR Kisaran is a multipurpose building utilized by the community for various activities, such as sports events, meetings, and wedding ceremonies. However, the thermal comfort within the building has been perceived as suboptimal by its users. This study aims to evaluate the building's thermal performance using the Overall Thermal Transfer Value (OTTV) approach, with a focus on the building envelope and solar radiation exposure. The calculation results indicate that the east and west façades have OTTV values exceeding the maximum limit of 35 W/m² as stipulated in SNI 03-6389-2020, reaching 58.9 W/m² and 67.3 W/m² respectively. The absence of shading devices on the glass façades is identified as the primary cause of excessive heat gain. The proposed solution involves the implementation of adaptive bamboo curtain walls, which are environmentally friendly, flexible, and cost-effective. This strategy is expected to reduce heat load, enhance thermal comfort, and promote energy efficiency in tropical buildings